2022
DOI: 10.3390/cancers14020414
|View full text |Cite
|
Sign up to set email alerts
|

The Alliance AMBUSH Trial: Rationale and Design

Abstract: Unlike medulloblastoma (MB) in children, robust prospective trials have not taken place for older patients due to the low incidence of MB in adults and adolescent and young adults (AYA). Current MB treatment paradigms for older patients have been extrapolated from the pediatric experience even though questions exist about the applicability of these approaches. Clinical and molecular classification of MB now provides better prognostication and is being incorporated in pediatric therapeutic trials. It has been e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Further studies with larger combined datasets that account for molecular features and variation in treatment strategies are needed to better understand which factors are most contributory to prolonging PFS and OS in adults with medulloblastoma. With growing access to targeted therapies and chemotherapeutic clinical trials (SJMB12, NCT01878617; SJDAWN, NCT03434262; PersoMed-I, NCT04402073; and Alliance AMBUSH Trial 40 ), and surgical trials (PBTC-053, NCT03904862) specifically including adults, subsequent studies must factor in optimal combinations of treatment modalities that include new targeted and immunotherapeutic approaches at recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies with larger combined datasets that account for molecular features and variation in treatment strategies are needed to better understand which factors are most contributory to prolonging PFS and OS in adults with medulloblastoma. With growing access to targeted therapies and chemotherapeutic clinical trials (SJMB12, NCT01878617; SJDAWN, NCT03434262; PersoMed-I, NCT04402073; and Alliance AMBUSH Trial 40 ), and surgical trials (PBTC-053, NCT03904862) specifically including adults, subsequent studies must factor in optimal combinations of treatment modalities that include new targeted and immunotherapeutic approaches at recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…We suspect that the benefit of these management practices could not be adequately assessed given relatively minimal duration from time of diagnosis. Future studies will provide insight into possible survival impact with less long-term morbidity, including the Alliance AM-BUSH Trial 43 and PersoMed-I trial (NCT04402073). A large phase 3 trial in children (ACNS0331; NCT00085735) showed that tumor bed (involved field) was noninferior (event-free survival) to PF boost RT, supporting the use of a more targeted boost that may limit therapy-related comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…While histopathological MB features are nearly indistinguishable from those observed in children, the distribution of molecular types is markedly different, with SHH-activated MB representing by far the most common molecular group in adults [ 35 ].…”
Section: Molecular Geneticsmentioning
confidence: 99%
“…To date, whole-genome methylation profiling is considered the gold standard diagnostic method, has been obtained mainly in children while these methylation data in adults is limited [ 41 , 42 , 45 ]. Comparative studies are being added to MB clinical trials in adults to further define the optimal diagnostic approach [ 35 ].…”
Section: Molecular Geneticsmentioning
confidence: 99%
See 1 more Smart Citation